The Role of Job Rotation in Improving Organizational Performance Field Study at Tishreen University - بركات حيان; عيسى جميل (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aimed to study the relationship between job rotation and organizational performance in administrative offices at Tishreen University, where job rotation is dealt with as one dimension. Whereas, organizational performance was measured through the two dimensions of efficiency and effectiveness. The questionnaire was used as a tool to collect data. The questionnaire was distributed to /363/ individual workers in the working administrative offices at Tishreen University, and the stability of the scale was confirmed by the Cronbach’s Alpha coefficient. In order to test the hypotheses, appropriate statistical methods were used where both researchers used descriptive statistics, a difference test for one sample ‘one sample t test’, and the Pearson test to test the linear correlation between the study variables. Through testing the hypotheses, a number of results were reached, including: The low level of job rotation and the low level of both efficiency and organizational effectiveness in the working administrative offices at Tishreen University. There is a moderate strength positive relationship between job rotation and organizational effectiveness. There is a strong positive relationship between job rotation and organizational efficiency.